2015
DOI: 10.1179/1743284714y.0000000628
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment 7: Quenching and partitioning

Abstract: Quenching and partitioning is a relatively new heat treatment concept to generate microstructures containing retained austenite stabilised by carbon partitioning from martensite. Research on quench and partitioning has been conducted by numerous groups, and this critical assessment provides some of the authors’ perspectives on progress and understanding in the field, with particular focus on the physical metallurgy and transformation mechanisms, process variations, mechanical behaviour, and industrial implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 94 publications
(155 reference statements)
2
64
0
2
Order By: Relevance
“…Addition of elements, such as Si, retards the formation of carbides and gives rise to the carbon enrichment of austenite (Santofimia et al, 2008;Paravicini Bagliani et al, 2013). Moreover, increased manganese levels have been shown to be effective at reporting significant austenite fractions with improved tensile properties in Q&P steels (De Moor et al, 2011;Speer et al, 2014). Mechanical property studies indicate that Q&P shows significant potential to generate novel property combinations that would otherwise be difficult in low alloy compositions (Speer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of elements, such as Si, retards the formation of carbides and gives rise to the carbon enrichment of austenite (Santofimia et al, 2008;Paravicini Bagliani et al, 2013). Moreover, increased manganese levels have been shown to be effective at reporting significant austenite fractions with improved tensile properties in Q&P steels (De Moor et al, 2011;Speer et al, 2014). Mechanical property studies indicate that Q&P shows significant potential to generate novel property combinations that would otherwise be difficult in low alloy compositions (Speer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased manganese levels have been shown to be effective at reporting significant austenite fractions with improved tensile properties in Q&P steels (De Moor et al, 2011;Speer et al, 2014). Mechanical property studies indicate that Q&P shows significant potential to generate novel property combinations that would otherwise be difficult in low alloy compositions (Speer et al, 2014). Fundamental understanding of the property -microstructure relationships in this type of steels has not been achieved, which is required for further improvement of the properties via intelligent microstructural design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…leads to unique mechanical properties. The martensite and bainite constituents contribute to an increase of strength, whereas RA provides an improvement of ductility [1]. The microstructural heterogeneity results also in significant stress and strain partitioning among the micro-constituents during plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Since then, synchrotron X-ray studies of the same have been reported 26 where it is found that carbon first partitions from martensite to austenite during tempering -this, of course, is a widely known phenomenon, 27 reflected also in the design of quenching and partitioning steels. 28 Lejay et al 29 now report results from a combination of synchrotron X-ray analysis and dilatometry where they characterise the dimensional changes and relate them to phase fractions, accounting for the measured lattice parameter changes.…”
Section: H K D H Bhadeshiamentioning
confidence: 99%